New Zealand Academy of Sport - SPARC`s High Performance Network - Evaluation of centre performance and accountability - Limna, J. (4. International Forum on Elite Sport. Montreal, Canada, 26-28 July 2005, 2005)
PERFORMANCE INDICATORS ..Coaching Services -Satisfaction; ..Compliance -Financial, Operational, Communication; ..Other Support/Added Value; ..Support Services -Satisfaction, impact on training and competition; ..Business Development.